Can immune-related genotypes illuminate the immunopathogenesis of cytomegalovirus disease in human immunodeficiency virus-infected patients? - Affandi, J.; Aghafar, Z.; Rodriguez, B.; Lederman, M.; Burrows, S.; Senitzer, D.; Price, Patricia (2012)
Most human immunodeficiency virus (HIV) patients are seropositive for cytomegalovirus (CMV) but a smaller proportion experience end-organ disease. This observation may reflect variations in genes affecting inflammatory and natural killer cell responses. DNA samples were collected from 240 HIV-infected patients followed at the University Hospitals/Case Medical Center (Cleveland, OH) between 1993 and 2008. Seventy-eight patients (African Americans = 41, Caucasians = 37) experienced CMV disease. Genotypes were determined using allele-specific fluorescent probes or multiplex polymerase chain reaction sequence-specific primers. IL12B3'UTR*(1) and SLC11A1 D543N*(1,2) were associated with CMV disease in African American patients (p = 0.04 and p = 0.02, respectively). IL10-1082*(1,2) and LILRB1 I142T*(1) were associated with CMV disease in Caucasians (p = 0.02 and p = 0.07, respectively). DARC T-46C*(1) and CD14 C-159T*(2) were associated with low nadir CD4 + T cell counts in African American patients (p = 0.002 and p = 0.01, respectively). Caucasian patients carrying TNFA-308*2, TNFA-1031*(2), IL2-330*(1), CCL2-2518*(2), or LILRB1 I142T*(1) had significantly lower nadir CD4 + T cells in a bootstrapped multivariable model (p = 0.006-0.02). In general, polymorphisms associated with CMV disease and CD4 + T cell counts were distinct in Caucasian and African American patients in the United States. The LILRB1 I142T polymorphism was associated with both CMV disease and low nadir CD4 + T cell counts in Caucasians, but the clearest determinant of low nadir CD4 + T cell count in African American patients was DARC T-46C. © 2012 American Society for Histocompatibility and Immunogenetics.